APAKAH SPIRITUALITAS DAN DUKUNGAN SOSIAL DAPAT MENINGKATKAN KEPUASAN HIDUP PADA MAHASISWA YANG TERGABUNG DALAM PERSEKUTUAN MAHASISWA KRISTEN? - Jesslyn Natania; Ersa Lanang Sanjaya (Universitas Gunadarma, 2023)
Individuals in the emerging adulthood stage will face many challenges and developmental tasks, those are the reasons why life satisfaction becomes important. Therefore, individuals need to understand several things that could increase their life satisfaction. This study aims to determine the effect of spirituality and social support on life satisfaction in students who are members of the Christian Students Community. Respondents in this study amounted to 153 students from 22 universities throughout Indonesia using purposive sampling technique. Analysis of the data used in this study is a multiple regression analysis test. Multiple regression test results show that there is an influence between spirituality and social support on life satisfaction with an effective contribution of 19.9%. This study also reviewed the role of each independent variable and found that social support had a significant effect on life satisfaction, while spirituality had no significant effect on student life satisfaction.